The Influence of Digital Literacy on The Use of Online Tutoring Systems According To Technology Acceptance Model (TAM) - Nur Eka Istikomah; Sudarno Sudarno; Muhammad Sabandi (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2024)
ABSTRACTThe grade of education in Indonesia is still in the "Medium" category and the low level of digital literacy indicates that the learning process in the classroom is not yet optimal. One form of effort that can be made to deal with this problem is by following the online tutoring system in the hope of improving their learning abilities so that they can improve results according to expectations. The purpose of this study is to determine the factors that can influence the use of an online tutoring system based on the Technology Acceptance Model (TAM). Some researchers try to add external variables with the aim of developing TAM theory. This research adds digital literacy factors that focus on students as new research. The population of this research was 9,042 senior high school students in Surakarta and 270 students were used as samples. This study used a quantitative method. Research data was collected by spreading questionnaires online with GForm. The data collection technique used was non-probability sampling with a purposive sampling approach. Data analysis was carried out using hierarchical regression analysis and the Sobel test. The research results show that perceived usefulness, ease of use, and digital literacy have a positive influence on the use of online tutoring systems. Digital literacy has also been proven to have an influence on perceptions of usefulness and ease of use. Then perceived usefulness and ease of use were also attested to mediate the connection between digital literacy and the use of online tutoring systems.Keywords: Digital Literacy, Online Tutoring System, TAM